Legal Views on the Development of International Law and the International Judicial System - Pratomo, Inge Widya Pangestika (Universitas Negeri Semarang, 2019)
Current law enforcement efforts are useful for combating international crime, so that the international community is not enough to do extradition treaties. It is also necessary to review the tendency of countries in combating international criminals who prefer to use with other agreements that are not less important and closely related to the cases that occur in the present. In relation, international law is emerging and created because of an international society, therefore it is society that should be the basis for the establishment of international law. The international community is also used as a sociological foundation in the formation of international law. The international community today comprises a number of equally independent and independent countries in the world that have interests to engage in international relations in a concerted and ongoing manner. This international relationship also arises because of the mutual need factor between countries in various interests, such as political interests, economics, culture, science, social and many more interests in the international community that can be used as a basis or can cause relations between countries . To be able to regulate international relations is required law that aims to ensure the existence of legal certainty in the international community. The law is also used as a basis for mentertibkan and mencipkatakan security in conducting relationships between countries so that no parties who feel harmed again.